2016
DOI: 10.1186/s12917-016-0696-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of a new real-time polymerase chain reaction assay for surveillance studies of lymphocystis disease virus in farmed gilthead seabream

Abstract: BackgroundLymphocystis disease (LCD) is the main viral infection reported to affect cultured gilthead seabream (Sparus aurata) in Europe. The existence of subclinical Lymphocystis disease virus (LCDV) infection in this fish species has been recognised by using polymerase chain reaction (PCR)-based methods. Nevertheless, these methods do not provide quantitative results that can be useful in epidemiological and pathological studies. Moreover, carrier fish have been involved in viral transmission, therefore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
3
23
0
1
Order By: Relevance
“…Moreover, the numbers of LCDV DNA copies were calculated to determine the correlation with the severity of clinical signs. The qPCR analysis confirmed that all animals were positive to viral MCP protein [8], as expected by the lesions, although with a huge range of variation in viral loads. Moreover, the high correlation (>90%) between LCDV DNA copies and the four SI categories confirmed this index is a good indicator of viral replication.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, the numbers of LCDV DNA copies were calculated to determine the correlation with the severity of clinical signs. The qPCR analysis confirmed that all animals were positive to viral MCP protein [8], as expected by the lesions, although with a huge range of variation in viral loads. Moreover, the high correlation (>90%) between LCDV DNA copies and the four SI categories confirmed this index is a good indicator of viral replication.…”
Section: Discussionsupporting
confidence: 64%
“…Several approaches have been established to control LCDV outbreaks in the hatcheries in the absence of efficient commercial vaccines. The most widespread approach is the monitoring and removal of asymptomatic carriers by using highly sensitive diagnostic methods [7,8]. This strategy has been successfully applied to prevent vertical transmission, but it requires a continuous evaluation of broodstocks and does not prevent horizontal transmission.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previously reported prevalence values of subclinical LCDV infections in gilthead sea bream juveniles, in which the quantitative PCR-estimated viral load in caudal fin ranged between 1 copy and 3.3 ϫ 10 2 copies of viral DNA per mg of tissue (58). In addition, 100% of a yellow perch population in Alberta (Canada) was found to contain LCDV, with only 2.6% of the fish showing lymphocystis lesions (59).…”
Section: Discussionsupporting
confidence: 79%
“…For many viral diseases, the RT‐qPCR could be used as a screening tool to establish viral‐free broodstock, to examine viral kinetics and to determine viral genome copies in asymptomatic carrier fish. For instance, asymptomatic carrier gilthead seabream containing lymphocystis disease virus were identified using a qPCR procedure (Valverde et al., ). Tissue distribution and target organs of red spotted grouper nervous necrosis virus were examined in juvenile European seabass ( Dicentrarchus labrax ) using RT‐qPCR, allowing the detection of viral replication in nervous and non‐nervous tissues (Lopez‐Jimena et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the RT-qPCR and conventional RT-PCR methods revealed that the qPCR technique provides 100 times greater sensitivity for the detection of infectious salmon anaemia virus (Munir & Kibenge, 2004). In addition, the RT-qPCR assay could be applied for virus screening in asymptomatic carriers or valuable broodstock (Hodneland et al, 2011;Valverde et al, 2016).…”
Section: Introductionmentioning
confidence: 99%